Polyimide and polyimide film
By developing a polyimide with excellent characteristics, the problems of poor dielectric properties, high water absorption rate and unfit CTE in the preparation of printed circuit boards are solved, and the effect of good dielectric properties after water absorption and the effect of matching CTE with metal foil is achieved.
Patent Information
- Application Number
- CN202410378268.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-15
- Filing Date
- 2024-03-29
- Publication Date
- 2025-03-18
AI Technical Summary
During the preparation process of printed circuit boards, existing polyimides have problems such as poor dielectric properties, excessive water absorption, inability to adapt to metal foils, and significant deterioration of dielectric properties after water absorption.
A polyimide derived from diacid anhydride and diamine was developed to obtain characteristic peaks A, B and C by Fourier conversion infrared spectroscopy (FTIR) attenuation total reflection method (ATR), and the ratio of characteristic peak areas was controlled to ensure that the polyimide had excellent dielectric properties, low water absorption and CTE suitable for metal foils.
The dielectric properties of polyimide are still good after water absorption, and are suitable as an insulating material for printed circuit boards. Its CTE is similar to metal foil, avoiding problems such as peeling or explosive boards.
Smart Images

Figure BDA0004767649240000131 
Figure BDA0004767649240000181 
Figure BDA0004767649240000182
Abstract
Description
Technical Field
[0001] The present invention relates to a polyimide, more particularly, to a polyimide having a specific Fourier transform infrared spectrum characteristic. The present invention also relates to a polyimide film. Background Art
[0002] In order to meet the requirements of high-frequency and high-speed transmission, the insulating materials used to prepare printed circuit boards must have a low dielectric constant (Dk) and a low dissipation factor (Df). Generally, the dielectric properties of insulating materials will deteriorate significantly due to the absorption of moisture. However, in the preparation process of printed circuit boards, the circuits will undergo processes such as blackening, washing and drying. Therefore, the insulating materials of printed circuit boards must still have good dielectric properties after undergoing processes such as water absorption and drying to maintain the characteristics of the printed circuit boards. In addition, the insulating materials of printed circuit boards need to have a coefficient of thermal expansion (CTE) similar to that of metal foil (e.g., copper foil) to avoid peeling or bursting during the manufacturing process of printed circuit boards.
[0003] It is known that polyimide can be used as an insulating material for preparing printed circuit boards. However, existing polyimide has technical problems such as poor dielectric properties, excessive water absorption, CTE incompatibility with metal foil, and obvious deterioration of dielectric properties after water absorption, and further improvement is still needed. Summary of the invention
[0004] In view of this, the present invention provides a polyimide derived from dianhydride and diamine, which has excellent dielectric properties, low water absorption, and CTE adapted to metal foil. Moreover, the dielectric properties of the polyimide will not be significantly deteriorated after absorbing water, and is particularly suitable as an insulating material for printed circuit boards.
[0005] Therefore, an object of the present invention is to provide a polyimide comprising repeating units derived from a dianhydride and repeating units derived from a diamine, wherein the polyimide has an infrared absorption spectrum obtained by Fourier transform infrared spectroscopy (FTIR) with attenuated total reflectance (ATR) at 1753 cm -1 To 1803cm -1 The characteristic peak A at 1635cm -1 Up to 1752cm -1 The characteristic peak B at 1160 cm -1 Up to 1170cm-1 The characteristic peak A has a characteristic peak area a, the characteristic peak B has a characteristic peak area b, the characteristic peak C has a characteristic peak area c, and b / a is not greater than 25.00, and c / b is not less than 0.3000.
[0006] In some embodiments of the present invention, 10.00≤b / a≤25.00.
[0007] In some embodiments of the present invention, 10.00≤b / a≤18.50.
[0008] In some embodiments of the present invention, 0.32≤c / b≤0.54.
[0009] In some embodiments of the present invention, 0.34≤c / b≤0.52.
[0010] In some embodiments of the present invention, FTIR is measured under the following conditions: ZnSe is used as the attenuated total reflection crystal, and the scanning range is 650 cm -1 Up to 4000cm -1 , the number of scans is 8 times.
[0011] In some embodiments of the present invention, the repeating unit derived from a diamine comprises a repeating unit derived from an aliphatic diamine.
[0012] In some embodiments of the present invention, the repeating unit derived from a diamine comprises a repeating unit derived from an aliphatic diamine and a repeating unit derived from an aromatic diamine.
[0013] In some embodiments of the present invention, the repeating units derived from a dianhydride include repeating units derived from an aromatic dianhydride.
[0014] In some embodiments of the present invention, the polyimide polymer backbone comprises ester functional groups.
[0015] In some embodiments of the present invention, the ratio of the number of ester functional groups to the number of imide functional groups, based on the total number of all functional groups of the polyimide, is not less than 0.8.
[0016] Another object of the present invention is to provide a polyimide film, which is made from the polyimide as described above.
[0017] In order to make the above-mentioned objectives, technical features and advantages of the present invention more obvious and easy to understand, some specific implementation schemes are described in detail below. DETAILED DESCRIPTION
[0018] Some specific embodiments according to the present invention will be described in detail below; however, the present invention can also be practiced in a variety of different forms, and the protection scope of the present invention should not be limited to the specific embodiments.
[0019] Unless otherwise stated, the terms "a", "an", "the" and similar terms used in the specification and claims should be understood to include both the singular and the plural.
[0020] The present invention has the advantages over the prior art in that the polyimide has excellent dielectric properties, low water absorption, and a CTE that is compatible with the metal foil (i.e., a CTE that is close to that of the metal foil), and has good dielectric properties after absorbing water. The following provides a detailed description of the polyimide of the present invention and its related applications.
[0021] 1. Polyimide
[0022] 1.1. Properties of polyimide
[0023] The polyimide of the present invention has a specific infrared absorption spectrum, which is obtained by Fourier transform infrared spectroscopy (FTIR) with attenuated total reflectance (ATR). The infrared absorption spectrum of the polyimide of the present invention has a wavelength of 1753 cm -1 To 1803cm -1 The characteristic peak A at 1635cm -1 Up to 1752cm -1 The characteristic peak B at 1160 cm -1 Up to 1170cm -1 The characteristic peak A has a characteristic peak area a, the characteristic peak B has a characteristic peak area b, and the characteristic peak C has a characteristic peak area c.
[0024] In the infrared absorption spectrum of the polyimide of the present invention, b / a is not greater than 25.00. For example, b / a may be 25.00, 24.75, 24.50, 24.25, 24.00, 23.75, 23.50, 23.25, 23.00, 22.75, 22.50, 22.25, 22.00, 21.75, 21.50, 21.25, 21.00, 20.75, 20.50, 20.25, 20.00, 19.75, 19.50, 19. .25, 19.00, 18.75, 18.50, 18.40, 18.25, 18.00, 17.75, 17.50, 17.25, 17.00, 16.75, 16.50, 16.25, 16.00, 15.75, 15.50, 15.25, 15.00, 14.75, 14.50, 14.25, 14.00, 13.75, 13.50, 13. 25, 13.00, 12.75, 12.50, 12.25, 12.00, 11.75, 11.50, 11.25, 11.00, 10.75, 10.50, 10.25, 10.05, 10.00, 9.75, 9.50, 9.25, 9.00, 8.75, 8.50, 8.25, 8.00, 7.75, 7.50, 7.25, 7.00, 6.7 5, 6.50, 6.25, 6.00, 5.75, 5.50, 5.25, 5.00, 4.75, 4.50, 4.25, 4.00, 3.75, 3.50, 3.25, 3.00, 2.75, 2.50, 2.25, 2.00, 1.75, 1.50, 1.25, 1.00, 0.75, 0.50, or 0.25, or within a range consisting of any two of the foregoing values. In some embodiments of the present invention, 10.00≤b / a≤25.00, more specifically 10.00≤b / a≤18.50, and even more specifically 10.05≤b / a≤18.40. If the b / a value of the polyimide falls outside the specified range, the CTE of the polyimide cannot be adapted to the copper foil, and the dielectric properties after water absorption are significantly deteriorated.
[0025] In the infrared absorption spectrum of the polyimide of the present invention, c / b is not less than 0.3000. For example, c / b may be 0.3000, 0.3100, 0.3200, 0.3300, 0.3350, 0.3400, 0.3450, 0.3500, 0.3600, 0.3700, 0.3800, 0.3900, 0.4000, 0.4100, 0.4200, 0.4300, 0.4400, 0.4500. , 0.4600, 0.4700, 0.4800, 0.4900, 0.5000, 0.5100, 0.5200, 0.5300, 0.5400, 0.5500, 0.5600, 0.5700, 0.5800, 0.5900, 0.6000, 0.6100, 0.6200, 0.6300, 0.6400, 0 .6500, 0.6600, 0.6700, 0.6800, 0.6900, 0.7000, 0.7100, 0.7200, 0.7300, 0.7400, 0.7500, 0.7600, 0.7700, 0.7800, 0.7900, 0.8000, 0.8100, 0.8200, 0.8300, 0.8 400, 0.8500, 0.8600, 0.8700, 0.8800, 0.8900, 0.9000, 0.9100, 0.9200, 0.9300, 0.9400, 0.9500, 0.9600, 0.9700, 0.9800, 0.9900, or 1.0000, or within a range consisting of any two of the foregoing values. In some embodiments of the present invention, 0.32≤c / b≤0.54, more specifically 0.34≤c / b≤0.52, and even more specifically 0.345≤c / b≤0.52. If the c / b value in the infrared absorption spectrum of the polyimide falls outside the specified range, the polyimide cannot have a CTE close to that of the copper foil and the dielectric properties of the polyimide after absorbing water are significantly deteriorated.
[0026] The FTIR was measured under the following conditions: ZnSe was used as the attenuated total reflection crystal, and the scanning range was 650 cm -1 Up to 4000cm -1 , the number of scans is 8, the resolution is 1cm -1 The instrument used for FTIR was an infrared spectrometer purchased from Perkin Elmer (model: FTIR spectrometer spectrum two), and the fixture was an ATR fixture purchased from PIKE Technologies (model: MIRacle TMSingle ReflectionATR), and the software used to analyze the FTIR results was Perkin Elmer 10.5.3.738, wherein the starting point, apex and end point of the characteristic peak were selected by the software (the point that was 0 after a first differentiation was selected), and then the area from the starting point to the apex to the end point was used as the integration range, and the characteristic peak area was calculated by the software.
[0027] 1.2. Structure and preparation of polyimide
[0028] Generally speaking, the synthesis method of polyimide can include a two-stage condensation method and a one-stage condensation method. The two-stage condensation method usually forms polyamic acid (PAA) by condensation polymerization of dianhydride and diamine, and then heats the polyamic acid to dehydrate and close the ring to form polyimide. The one-stage condensation method usually forms polyimide by reacting dianhydride and diisocyanate at high temperature.
[0029] The preparation method of the polyimide of the present invention is not particularly limited. In some embodiments of the present invention, the polyimide is formed by polymerizing dianhydride and diamine by a two-stage condensation method, and thus comprises repeating units derived from dianhydride and repeating units derived from diamine. Specifically, the diamine is first placed in a flask under a nitrogen atmosphere, and a solvent is added to completely dissolve the diamine, and then the dianhydride is added, and the intermediate solution is stirred at room temperature for 12 hours to obtain a polyamic acid solution, and then the polyamic acid is subjected to a thermal ring-closure reaction at a high temperature to obtain a polyimide. The preparation of the polyimide of the present invention is preferably carried out under the following conditions: (1) based on the total amount of diamine, the amount of long carbon chain aliphatic diamine is preferably not more than 20 mol%; and (2) based on the total number of all functional groups of the polyimide, the ratio of the number of ester functional groups to the number of imide functional groups is 0.8 to 2.0.
[0030] The types of dianhydrides that can be used to form the polyimide of the present invention are not particularly limited, and examples thereof include, but are not limited to, 2,3,3',4'-biphenyltetracarboxylic dianhydride (a-BPDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (s-BPDA), pyromellitic dianhydride (PMDA), 1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxylic acid-1,4-phenyl ester (TAHQ), 4,4'-bisphenol A dianhydride (4,4'-bisphenol A dianhydride). Adianhydride (BPADA), 4,4'-oxydiphthalic anhydride (ODPA), 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA), and hydroquinone diphthalic anhydride (HQDA). Each of the above-mentioned dianhydrides can be used alone or in combination. In some embodiments of the present invention, the repeating unit derived from the dianhydride includes a repeating unit derived from an aromatic dianhydride, and the aromatic dianhydride can be selected from the following group: a-BPDA, s-BPDA, TAHQ, BTDA, ODPA, and combinations thereof.
[0031] There is no particular limitation on the type of diamine that can be used to form the polyimide of the present invention, and the diamine can be selected from aliphatic diamines and aromatic diamines. Examples of the aliphatic diamine include, but are not limited to, 1,2-ethylenediamine, 1,2-propylenediamine, 1,3-diaminopropane, 1,5-diaminopentane, 1,4-bis(aminomethyl)cyclohexane, 4,4'-methylenebis(2-methylcyclohexylamine), octamethylendiamine (OMDA), isophoronediamine (IPDA), 4,4'-diaminodicyclohexylmethane (4,4'-diaminodicyclohexylamine), 4,4'-diaminodicyclohexylamine (4,4'-diaminodicyclohexylamine), 4,4'-diaminodicyclohexylmethane ... methane), hexamethylenediamine (HMDA), octamethylenediamine (OMDA), 3,3'-dimethyl-4,4'-diamino-dicyclohexyl-methane, C36 dimer diamine (C36 DDA), C38 dimer diamine, and C40 dimer diamine. Examples of the dimer diamine include dimer diamines derived from oleic acid, linoleic acid, linolenic acid, palmitoleic acid, or elaidic acid, such as Priamine 1074 or Priamine 1075 products available from Croda. The aforementioned aliphatic diamines can be used alone or in combination. Examples of the aromatic diamines include, but are not limited to, bis(4-aminophenyl)terephthalate (BPTP), 1,4-bis(4-aminobenzoyloxy)benzene (ABHQ), 4-aminophenyl-4-aminobenzoate (APAB), 4,4'-oxydianiline ,ODA), p-phenylenediamine (PPD), bis(4-aminophenyl)deca-hydronaphthalene-2,6-dicarboxylate (ET-BDM), 2,7-bis(4-aminophenoxy)naphthalene (ET-2,7-Na), N,N'-(4,4'-(9H-fluorene-9,9-diyl)bis(4,1-phenylene))bis(4-aminobenzamide)(FDA-ADA), 4,4'-(hexafluoroisopropylidene)dianiline(6FPDA), 4,4'-(hexafluoroisopropylidene)bis(p-phenyleneoxy)dianiline(BAPHF), bis[4-(3-aminophenoxy)phenyl]sulfone(BAPS), 4,4'-diaminobenzanilide(DAB A), N1,N4-bis(4-aminophenyl)-terephthalamide (BPTPA), 4,4'-(4,4'-oxybis(4,1-phenylene)bis(oxy))bis(3-(trifluoromethyl)-aniline) (p-6FAPE), and bis(4-aminophenyl)-cyclohexane-1,4-dicarboxylate (ES-C). The above aromatic diamines may be used alone or in combination of two or more. In one embodiment of the present invention, the polyimide comprises repeating units derived from an aliphatic diamine. In another embodiment of the present invention, the polyimide comprises repeating units derived from an aliphatic diamine and repeating units derived from an aromatic diamine. The aliphatic diamine is preferably a long carbon chain aliphatic diamine, and the aliphatic diamine and the aromatic diamine can be selected from the following group: PPD, ODA, C36 DDA, ABHQ, BPTP, and combinations thereof.
[0032] Examples of solvents that can be used to dissolve the dianhydride and the diamine include, but are not limited to, N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (N,N-dimethylformamide), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), acetonitrile, hexamethylphosphoric triamide (HMPA), and 1,3-dimethyl-2-imidazolidinone (DMI). The solvents can be used alone or in any combination.
[0033] In some embodiments of the present invention, the polyimide comprises ester functional groups in the polymer backbone. The polyimide can be formed by polymerizing a dianhydride containing an ester functional group and a diamine, a dianhydride and a diamine containing an ester functional group, or a dianhydride containing an ester functional group and a diamine containing an ester functional group. Examples of the dianhydride containing an ester functional group include, but are not limited to, TAHQ, and examples of the diamine containing an ester functional group include, but are not limited to, ABHQ, APAB, and BPTP.
[0034] In a preferred embodiment of the present invention, based on the total number of all functional groups of the polyimide, the ratio of the number of ester functional groups to the number of imide functional groups is not less than 0.8, preferably 0.8 to 2.0, for example, 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, or 2.0, or within the range formed by any two of the above values. If the ratio of the number of ester functional groups to the number of imide functional groups of the polyimide is 0.8 or more, the dielectric properties of the polyimide and the dielectric properties after water absorption can be further improved.
[0035] 2. Polyimide film
[0036] The polyimide of the present invention can be used to form a film product. Therefore, the present invention also relates to a polyimide film. The formation method of the polyimide film of the present invention is not particularly limited. The film can be formed by coating the polyimide with an existing coating method in the technical field to which the present invention belongs, or, after the polyamic acid solution is coated with an existing coating method in the technical field to which the present invention belongs to form a polyamic acid film, the polyamic acid film is heated to form a polyimide film so that the polyamic acid is thermally closed. Examples of the existing coating methods include, but are not limited to, roller coating, blade coating, comma coating, mold coating, slit coating, wire rod coating, and spray coating.
[0037] In some embodiments of the present invention, a polyimide film is prepared in the following manner. First, a polyamic acid solution is filtered to remove dust and impurities. Then, the polyamic acid solution is applied to a cleaned glass substrate using a scraper mold. Afterwards, the glass substrate coated with the polyamic acid solution is placed in a vacuum environment for 4 to 8 hours to slowly remove the solvent. Then, the glass substrate is placed in a high temperature and vacuum oven to allow the polyamic acid to undergo a thermal ring-closure reaction to form polyimide, thereby obtaining a polyimide film. Afterwards, the temperature is slowly lowered and then several stages of heat treatment are performed at a temperature of 100° C. to 500° C. to stabilize the properties of the polyimide film, and finally the polyimide film is slowly cooled to room temperature to avoid film rupture.
[0038] The polyimide film of the present invention has excellent dielectric properties, low water absorption, and CTE close to that of metal foil, and the dielectric properties after water absorption are still good, and is particularly suitable as an insulating material for printed circuit boards. The thickness of the polyimide film of the present invention is preferably 10 μm to 50 μm, for example, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, 30 μm, 31 μm, 32 μm, 33 μm, 34 μm, 35 μm, 36 μm, 37 μm, 38 μm, 39 μm, 40 μm, 41 μm, 42 μm, 43 μm, 44 μm, 45 μm, 46 μm, 47 μm, 48 μm, 49 μm, or 50 μm, or within the range consisting of any two of the above values.
[0039] 3. Example
[0040] 3.1. Measurement method
[0041] The present invention is further illustrated by the following specific embodiments, wherein the measuring instruments and methods used are as follows:
[0042] [FTIR analysis]
[0043] Prepare a polyimide film with a length of 5 cm, a width of 5 cm and a thickness of at least 10 μm as a test piece. Put the test piece into an infrared spectrometer (model: FTIR spectrometer spectrum two) and use an ATR fixture (model: MIRacle TM Single Reflection ATR) and configured with analysis software Perkin Elmer 10.5.3.738, FTIR analysis was performed under the following conditions: ZnSe was used as the attenuated total reflection crystal, and the scanning range was 650 cm -1 Up to 4000cm -1 , the number of scans is 8, the resolution is 1cm -1 .
[0044] In the infrared absorption spectrum of the obtained polyimide, the software is used to select the point where the first differential is 0 as the characteristic peak starting point, characteristic peak vertex and characteristic peak end point, and then the area from the starting point to the vertex to the end point is used as the integration range to calculate the characteristic peak area using the software.
[0045] [Dielectric property measurement]
[0046] A polyimide film specimen with a length of 8 cm, a width of 8 cm and a thickness of at least 10 μm was vacuum dried at 100°C for 24 hours, and then the dielectric constant (Dk) and the loss factor (Df) of the dried specimen were measured to obtain the dielectric properties before water absorption. The measurement was performed using a vector network analyzer (model: ZVB, purchased from Rohde & Schwarz) was performed at an analysis frequency of 10 gigahertz (GHz).
[0047] In addition, a polyimide film test piece with a length of 8 cm, a width of 8 cm and a thickness of at least 10 μm was immersed in water for 24 hours and then wiped dry, and the above-mentioned steps of measuring Dk and Df were performed to obtain the dielectric properties after water absorption.
[0048] [Water absorption test]
[0049] The water absorption of the polyimide film is measured with reference to the specification of IPC-TM-650 2.6.2.1 and calculated by the following formula, wherein W1 represents the weight of the polyimide film after drying in an oven at 105°C for 1 hour, and W2 represents the weight of the polyimide film after wiping off the water droplets on the film after soaking in water at 23°C for 24 hours. The test piece of the polyimide film has a length of 2 inches, a width of 2 inches, and a thickness of 25 microns.
[0050]
[0051] [Measurement of coefficient of thermal expansion (CTE)]
[0052] The CTE of the polyimide film was measured using a thermomechanical analyzer (model: TMA Q400, purchased from TA Instruments). The measurement conditions are as follows: the polyimide film test piece used for measurement has a length of 10 mm, a width of 5 mm, and a thickness of 20 μm, the atmosphere is a dry nitrogen atmosphere, and the test temperature range of CTE is 50° C. to 300° C. The unit of CTE is ppm / K.
[0053] 3.2. Preparation of polyamic acid solution
[0054] [Example 1]
[0055] First, 7.11 g (0.0204 mol) of ABHQ (purchased from Shifeng Company) and 1.21 g (0.0023 mol) of C36 DDA (model: Priamine 1074, purchased from Croda Company) were placed in a flask, and 85 ml of anhydrous DMAc was added, stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Then, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. After that, 6.68 g (0.0227 mol) of s-BPDA (purchased from UBE Company) was added to the intermediate solution and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved to obtain the polyamic acid solution of Example 1.
[0056] [Example 2]
[0057] First, 6.15 g (0.0177 mol) of ABHQ and 2.36 g (0.0044 mol) of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Then, the intermediate solution was placed in an ice-water bath, 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. After that, 6.49 g (0.0221 mol) of s-BPDA was added to the intermediate solution and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved to obtain the polyamic acid solution of Example 2.
[0058] [Example 3]
[0059] First, 6.15 g (0.0177 mol) of BPTP (purchased from Shifeng Company) and 2.36 g (0.0044 mol) of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Then, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. After that, 6.49 g (0.0221 mol) of s-BPDA was added to the intermediate solution and stirred at room temperature for 15 hours. After that, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved to obtain the polyamic acid solution of Example 3.
[0060] [Example 4]
[0061] First, 1.91 g (0.0177 mol) of PPD (purchased from Shifeng Company) and 1.52 g (0.0076 mol) of ODA (purchased from Liyongfa Company) were placed in a flask, and 85 ml of anhydrous DMAc was added, stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 10% by weight. Then, the intermediate solution was placed in an ice water bath, and 5.5 mmoles of glacial acetic acid were slowly dripped in, and stirred for 10 minutes. After that, 11.57 g (0.0252 mol) of TAHQ (purchased from Shifeng Company) was added to the intermediate solution and stirred at room temperature for 15 hours. After that, 0.05 mmoles of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved to obtain the polyamic acid solution of Example 4.
[0062] [Example 5]
[0063] First, 5.8 g (0.0167 mol) of ABHQ and 0.99 g (0.0019 mol) of C36 DDA were placed in a flask, and 85 ml of anhydrous DMAc was added, stirred and dissolved at 80 ° C, and a concentration of 15% by weight of the intermediate solution was prepared. Then, the intermediate solution was placed in an ice water bath, and 5.5 mmoles of glacial acetic acid were slowly dripped in, and stirred for 10 minutes. After that, 7.63 g (0.0167 mol) of TAHQ and 0.57 g (0.0019 mol) of ODPA (purchased from Liyongfa Company) were added to the intermediate solution and stirred at room temperature for 15 hours. After that, 0.05 mmoles of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved to obtain the polyamic acid solution of Example 5.
[0064] [Comparative Example 1]
[0065] First, 8.13 g (0.0233 mol) of BPTP was placed in a flask, and 85 ml of anhydrous DMAc was added, stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Then, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. Afterwards, 6.87 g (0.0233 mol) of s-BPDA was added to the intermediate solution, and stirred at room temperature for 15 hours. Afterwards, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Comparative Example 1 was obtained.
[0066] [Comparative Example 2]
[0067] First, 8.13 g (0.0233 mol) of ABHQ was placed in a flask, and 85 ml of anhydrous DMAc was added, stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Then, the intermediate solution was placed in an ice-water bath, and 5.5 mmoles of glacial acetic acid were slowly dripped in, and stirred for 10 minutes. Afterwards, 6.87 g (0.0233 mol) of s-BPDA was added to the intermediate solution, and stirred at room temperature for 15 hours. Afterwards, 0.05 mmoles of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Comparative Example 2 was obtained.
[0068] [Comparative Example 3]
[0069] First, 6.48 g (0.0186 mol) of BPTP was placed in a flask, and 85 ml of anhydrous DMAc was added, stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Then, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. Afterwards, 8.52 g (0.0186 mol) of TAHQ was added to the intermediate solution, and stirred at room temperature for 15 hours. Afterwards, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Comparative Example 3 was obtained.
[0070] [Comparative Example 4]
[0071] First, 6.48 g (0.0186 mol) of ABHQ was placed in a flask, and 85 ml of anhydrous DMAc was added, stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 15% by weight. Then, the intermediate solution was placed in an ice-water bath, and 5.5 mmoles of glacial acetic acid were slowly dripped in, and stirred for 10 minutes. Afterwards, 8.52 g (0.0186 mol) of TAHQ was added to the intermediate solution, and stirred at room temperature for 15 hours. Afterwards, 0.05 mmoles of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Comparative Example 4 was obtained.
[0072] [Comparative Example 5]
[0073] First, 6.07 g (0.0303 mol) of ODA was placed in a flask, and 85 ml of anhydrous DMAc was added, stirred and dissolved at 80°C to prepare an intermediate solution with a concentration of 10% by weight. Then, the intermediate solution was placed in an ice-water bath, and 5.5 mmol of glacial acetic acid was slowly dripped in, and stirred for 10 minutes. Afterwards, 8.93 g (0.0303 mol) of s-BPDA was added to the intermediate solution, and stirred at room temperature for 15 hours. Afterwards, 0.05 mmol of acetic anhydride was added as a ring-closing agent, and stirred for 30 minutes to confirm that the acetic anhydride was completely dissolved, and the polyamic acid solution of Comparative Example 5 was obtained.
[0074] 3.3. Preparation of polyimide membrane
[0075] The polyamic acid solution of embodiments 1 to 5 and comparative examples 1 to 5 is used to prepare polyimide film. First, a filter head of 0.45 micron is used to filter the polyamic acid solution to remove dust and impurities. Then, the polyamic acid solution is applied to a cleaned glass substrate (length 20 cm, width 20 cm, thickness 0.5 cm) with a scraper mold of 600 microns. Afterwards, the glass substrate coated with the polyamic acid solution is placed in a vacuum environment for 6 hours to slowly remove the solvent. Then, the glass substrate coated with the polyamic acid solution is subjected to heat treatment for 1 hour at a temperature of 100°C, 200°C, 300°C and 350°C in sequence, so that the polyamic acid is subjected to a thermal ring-closure reaction to form a polyimide film, and the properties of the polyimide film are stabilized. Finally, in order to avoid film rupture, the temperature is slowly cooled to room temperature before taking out to obtain the polyimide film of embodiments 1 to 5 and comparative examples 1 to 5.
[0076] 3.4. FTIR, dielectric properties and CTE analysis of polyimide films
[0077] The properties of the polyimide films of Examples 1 to 5 and Comparative Examples 1 to 5 were measured according to the aforementioned measurement methods, including FTIR analysis, Dk, Df, and CTE, and the results are recorded in Tables 1 to 4.
[0078] Table 1: FTIR analysis of polyimide films of Examples
[0079]
[0080] Table 2: FTIR analysis of polyimide films of comparative examples
[0081]
[0082] Table 3: CTE of polyimide films of examples
[0083]
[0084] Table 4: Properties of polyimide films of comparative examples
[0085]
[0086] Taking into account the CTE of metal foil (e.g., copper foil) and adhesive resin, the CTE value of the polyimide film used to prepare printed circuit boards is preferably close to the CTE value of the metal foil, generally falling between about 10ppm / ℃ and 40ppm / ℃, preferably falling between about 20ppm / ℃ and 40ppm / ℃, so as to avoid peeling or bursting of the laminate during the processing of the laminate. As shown in Table 3, the polyimide film of the present invention not only has excellent Df and Dk values, but also has a CTE close to that of the metal foil. In contrast, as shown in Table 4, the polyimide film not belonging to the present invention cannot simultaneously have excellent Df, excellent Dk, and CTE adapted to the metal foil. In particular, Comparative Examples 1 and 2 show that if the c / b value of the polyimide is not within the specified range of the present invention, even if the b / a value is within the specified range of the present invention, the polyimide film does not have excellent dielectric properties and does not have a CTE adapted to the metal foil. Comparative Example 4 shows that if the b / a value of the polyimide is not within the specified range of the present invention, the polyimide film does not have a CTE that is compatible with the metal foil even if the c / b value is within the specified range of the present invention. Comparative Examples 3 and 5 show that if both the b / a value and the c / b value of the polyimide FTIR analysis are not within the specified range of the present invention, the polyimide film does not have a CTE that is compatible with the metal foil, and the CTE value of the polyimide film in Comparative Example 3 is even much lower than the CTE value of the metal foil.
[0087] 3.5. Dielectric properties and water absorption rate of polyimide films after water absorption
[0088] According to the measurement method described above, the Dk after water absorption, the Df after water absorption, and the water absorption rate of the polyimide films of Examples 1 to 3 and 5 and Comparative Examples 1 to 2 and 4 to 5 were further measured, and the results are recorded in Tables 5 to 6.
[0089] Table 5: Dielectric properties and water absorption of the polyimide films of the examples after water absorption
[0090]
[0091] Table 6: Dielectric properties and water absorption of the polyimide films of the comparative examples after water absorption
[0092]
[0093] As shown in Table 5, the polyimide film of the present invention has a low water absorption rate and still has good Df and Dk after absorbing water and drying, and is suitable as an insulating material for a printed circuit board. In contrast, as shown in Table 6, the polyimide film not belonging to the present invention does not have good Df and Dk after absorbing water and drying, and is not suitable as an insulating material for a printed circuit board.
[0094] The above embodiments are only used to illustrate the principle and efficacy of the present invention and to describe the technical features of the present invention, and are not intended to limit the scope of protection of the present invention. Any changes or arrangements that can be easily completed by a person familiar with the present technology without violating the technical principle of the present invention are within the scope of the present invention.
Claims
1. A polyimide, characterized in that: It comprises repeating units derived from dianhydride and repeating units derived from diamine, wherein the infrared absorption spectrum of the polyimide obtained by Fourier transform infrared spectroscopy with attenuated total reflection method has a peak at 1753 cm -1 To 1803cm -1 The characteristic peak A at 1635cm -1 Up to 1752cm -1 The characteristic peak B at 1160 cm -1 Up to 1170cm -1 The characteristic peak A has a characteristic peak area a, the characteristic peak B has a characteristic peak area b, the characteristic peak C has a characteristic peak area c, and b / a is not greater than 25.00, and c / b is not less than 0.3000.
2. The polyimide according to claim 1, characterized in that 10.00≤b / a≤25.
00.
3. The polyimide according to claim 2, characterized in that 10.00≤b / a≤18.
50.
4. The polyimide according to claim 1, characterized in that 0.32≤c / b≤0.
54.
5. The polyimide according to claim 4, characterized in that 0.34≤c / b≤0.
52.
6. The polyimide according to any one of claims 1 to 5, characterized in that Fourier transform infrared spectroscopy was performed under the following conditions: ZnSe was used as the attenuated total reflection crystal and the scanning range was 650 cm -1 Up to 4000cm -1 , the number of scans is 8 times.
7. The polyimide according to any one of claims 1 to 5, characterized in that The repeating unit derived from a diamine includes a repeating unit derived from an aliphatic diamine.
8. The polyimide according to claim 7, characterized in that The repeating unit derived from diamine also includes a repeating unit derived from an aromatic diamine.
9. The polyimide according to any one of claims 1 to 5, characterized in that The repeating unit derived from a dianhydride includes a repeating unit derived from an aromatic dianhydride.
10. The polyimide according to any one of claims 1 to 5, characterized in that The polyimide contains ester functional groups in the polymer backbone.
11. A polyimide film, characterized in that: The invention is prepared from the polyimide according to any one of claims 1 to 10.